The art of assembly language - Hyde, Randall (No Starch Press, 2010)
Widely respected by hackers of all kinds, The Art of Assembly Language teaches programmers how to understand assembly language and how to use it to write powerful, efficient code. Using the proven High Level Assembler (HLA) as its primary teaching tool, The Art of Assembly Language leverages your knowledge of high level programming languages to make it easier for you to quickly grasp basic assembly concepts. Among the most comprehensive references to assembly language ever published, The Art of Assembly Language, 2nd Edition has been thoroughly updated to reflect recent changes to the HLA lang.